REINTERPRETASI GENDER DALAM HUKUM ISLAM: ANALISIS KRITIS TERHADAP KEPEMIMPINAN PEREMPUAN, POLIGAMI, DAN KEWARISAN - Khalid, Iqbal Ibnu; Ningrum, Sulistia (Institut Dirosat Islamiyah Al-Amien Prenduan, 2025)
The discourse on gender in Islamic law continues to be a subject of academic interest, especially when religious practices in various Muslim communities still exhibit patriarchal biases that contribute to social inequality between men and women. This study attempts to reinterpret the concept of gender in Islamic law by examining three main issues, namely female leadership, polygamy, and inheritance. The research uses a library method with a critical-analytical approach through the integration of a gender hermeneutics framework, maq??id al-syar?‘ah, and historical-normative analysis of classical and contemporary sources. The results of the study show that a number of fiqh constructions regarding gender relations are more influenced by the social and patriarchal cultural context of pre-modern societies than by the normative principles of justice in the Qur'an. Maq??id-based reinterpretation affirms that justice, equality of dignity, and protection of rights are fundamental principles that can reframe the position of women in leadership, the practice of polygamy, and the distribution of inheritance. Furthermore, this study highlights the importance of a more comprehensive re-reading of religious texts, taking into account contemporary social dynamics, developments in legal thought, and the ethical demands of modern Muslim societies. Thus, this article not only provides a theoretical analysis but also offers a conceptual foundation for the development of a more adaptive and inclusive methodology of istinb?? law. This article contributes to strengthening the epistemology of Islamic law that is responsive to gender justice issues and opens up space for the development of fiqh that is more contextual, humanistic, and in line with universal human values.